Implementation of the Aceh Government’s Policy in Accelerating Land Registration for Low-Income Communities in Banda Aceh City - Dhira Fildzah; Syarifuddin Syarifuddin; Mazwar Mazwar (International Journal of Law, Crime and Justice, 2026)
Land registration is a legal instrument aimed at providing legal certainty and protection of land rights. In order to accelerate the legalization of assets owned by low-income communities, the Aceh Government, through the Aceh Land Office, implements a policy to accelerate land registration as part of its special authority in the land sector under Law Number 11 of 2006 concerning the Government of Aceh. However, its implementation still faces various obstacles that prevent low-income communities from fully accessing legal certainty over land rights. This study aims to analyze the implementation of the accelerated land registration policy for low-income communities in Banda Aceh City and the strategies adopted to address implementation barriers. The research method used is empirical legal research with a sociological juridical approach. Data were obtained through interviews with relevant stakeholders and supported by library research of laws and regulations, official documents, books, journals, and relevant legal literature. The findings show that the acceleration of land registration for low-income communities is carried out through the Land Administration Inventory Program for Low-Income Communities implemented by the Aceh Land Office and supports the Complete Systematic Land Registration (PTSL) Program. Its implementation involves coordination among various related institutions but still encounters obstacles such as budget limitations, suboptimal inter-agency coordination, limited implementation time, and difficult-to-reach target locations. Efforts to address these obstacles include strengthening institutional coordination, establishing Cooperation Agreements (MoU), optimizing available budgets, and enhancing the role of village governments in land data collection and administrative verification. It is recommended that the Aceh Government increase budget support, strengthen inter-agency coordination, expand institutional cooperation, and continuously update data on low-income communities to achieve more effective legal certainty and protection of land rights for the poor. Keywords: Policy Implementation, Aceh Government, Land Registration, Low-Income Communities, Legal Certainty.